Peranan Randai Ulu Ambek Dalam Acara Ulu Ambek Di Korong Kampuang Guci Pucuang Anam Kenagarian Tandikek Selatan Kecamatan Patamuan Kabupaten Padang Pariaman - Sintia Anisa; Darmawati Darmawati (SENDRATASIK UNP, 2021)
The research aims to reveal, describe and analyze about Randai's role in the event Ulu Ambek Korong Kampuang Guci Pucuang Anam kenagarian Tandikek Selatan District Patamuan Padang Pariaman Regency. This type of research is qualitative research with descriptive methods of analysis. The object of this research is the art of Randai Ulu Ambek in Kenagarian Tandikek Selatan District Patamuan Padang Pariaman Regency. The types of data in this study are primary data and secondary data. The main instrument is the researcher himself. Data collection techniques are performed by literature, observation, interview and documentation. The data is collected in the analysis with interpretation techniques so that it can be obtained the truth. The results of this study show that the role of Randai Ulu Ambek is very important in Ulu Ambek Event, it can be seen from the same conditions of Randai Ulu Ambek as Ulu Ambek. In randai ulu ambek movement are the basics of Ulu Ambek, as well as the accompaniment music in Randai Ulu Ambek is the same as Ulu Ambek. Randai Ulu Ambek performance venue is also the venue of Ulu Ambek which is called the matches. The dancers in Ulu Ambek are dancers who are already proficient in Randai Ulu Ambek as well as baligh. So the role of Randai Ulu Ambek is very important in ulu ambek performance, if randai ulu ambek performance is not performed then Ulu Ambek event does not take place because Randai Ulu Ambek as the opener asks permission to niniak mamak nagari respectively.